2021
DOI: 10.1097/wno.0000000000001385
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Breast Cancer Presenting as Progressive Ophthalmoplegia 30 Years After Initial Cancer Diagnosis

Abstract: :A 60 year-old woman presented with painless progressive ophthalmoplegia of the right eye. She had a history of left-sided breast carcinoma 30 years ago that was managed with mastectomy only, with appropriate serial follow-up investigations. On examination, her visual acuity was 20/400 in the right eye and 20/20 in the left. She had a right relative afferent pupillary defect. Ocular examination was significant for 2 mm of ptosis, complete ophthalmoplegia, and 2+ chemosis in the right eye. The left eye was norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…A review of cases involving bilateral orbital metastases from breast cancer, as reported in English-language literature, was conducted through PubMed, Medline, and Google Scholar databases using the appropriate controlled [MESH] keywords “breast cancer”, “bilateral”, “metastases”, “ocular” and “orbit” and acknowledging references list. The selected articles included case reports and case series that provided detailed clinical, histological, and treatment descriptions ( 30 , 42 , 47 , 48 , 50 77 ). The summarized findings are presented in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A review of cases involving bilateral orbital metastases from breast cancer, as reported in English-language literature, was conducted through PubMed, Medline, and Google Scholar databases using the appropriate controlled [MESH] keywords “breast cancer”, “bilateral”, “metastases”, “ocular” and “orbit” and acknowledging references list. The selected articles included case reports and case series that provided detailed clinical, histological, and treatment descriptions ( 30 , 42 , 47 , 48 , 50 77 ). The summarized findings are presented in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The mean age was 59 years (ranging from 36 to 83 years). The majority (64%) had known breast cancer ( 42 , 47 , 50 , 53 , 57 , 58 , 61 , 62 , 64 68 , 70 73 , 76 , 77 ), and orbital metastases were usually identified around 4.8 years after the first diagnosis. Due to the anatomical constraints of the compact orbit space, these metastases usually present as space-occupying lesions, leading to significant clinical symptoms ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations